Proceedings of CITA'05 : Fourth international conference on information technology in Asia 2005 - Yoe , Alvin W.; Kulathuramaiyer, Narayanan; Wang , Yin Chai; Tan, Chong Eng (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The issue of online profiling and privacy has received growing attention from academics and practitioners. The unprecedented race among e-businesses to provide personalised contents has placed distrust in consumers at an alarming rate. This study combines and applies well established constructs developed by (8,9,11) to empirically assess the existing scenario of Australian Website's with regards to online profiling, privacy and trust. The study further highlights relevant managerial implications for mananging these constructs and directions for future research are discussed, paart from suggesting an alternative approach towards online profiling i.e self-profiling.